Localization of Arabidopsis Glucan Synthase-Like 5, 8, and 12 to plasmodesmata and the GSL8-dependent role of PDLP5 in regulating plasmodesmal permeability - Behnaz Saatian; Susanne E. Kohalmi; Yuhai Cui (Plant Signaling & Behavior, 2023)
Cell-to-cell communication via membranous channels called plasmodesmata (PD) plays critical roles during plant development and in response to biotic and abiotic stresses. Several enzymes and receptor-like proteins (RLPs), including Arabidopsis thaliana glucan synthase-likes (GSLs), also known as callose synthases (CALSs), and PD-located proteins (PDLPs), have been implicated in plasmodesmal permeability regulation and intercellular communication. Localization of PDLPs to punctate structures at the cell periphery and their receptor-like identity have raised the hypothesis that PDLPs are involved in the regulation of symplastic trafficking during plant development and in response to endogenous and exogenous signals. Indeed, it was shown that PDLP5 could limit plasmodesmal permeability through inducing an increase in callose accumulation at PD. However, mechanistically, how this is achieved remains to be elucidated. To address this key issue in understanding the regulation of PD, physical and functional interactions between PDLPs and GSLs (using the PDLP5–GSL8/CALS10 pair as a model) were investigated. Our results show that GSL8/CALS10 plays essential roles and is required for the function and plasmodesmal localization of PDLP5. Furthermore, it was demonstrated that the localization of PDLP5 to PD and its function in inducing callose deposition are GSL8-dependent. Importantly, our transgenic study shows that three key members of the GSL family, i.e., GSL5/CALS12, GSL8/CALS10, and GSL12/CALS3, localize to PD and co-localize with PDLP5, suggesting that GSL8/CALS10 might not be the only callose synthase with the determining role in PD regulation. These findings, together with our previous observation showing the direct interaction of GSL8/CALS10 with PDLP5, indicate the pivotal role of the GSL8/CALS10-PDLP5 interplay in regulating PD permeability. Future work is needed to investigate whether the PDLP5 functionality and localization are also disrupted in gsl5 and gsl12, or it is just gsl8-specific.